Analisis Tingkat Kelelahan Postpartum terhadap Motivasi Pemberian ASI: Analysis of Postpartum Fatigue Levels on Breastfeeding Motivation - Hapsari, Elvina Amelia; Indrianingrum, Irawati; Azizah, Noor (Chakra Brahmanda Lentera Institute, 2026)
Exclusive breastfeeding is an essential intervention to improve infant health, yet its achievement in many regions remains below established targets. Postpartum mothers frequently experience fatigue resulting from physiological and psychological changes, insufficient rest, and the demands of adapting to a new maternal role, which may affect their motivation to breastfeed. The purpose of this study was to analyze the relationship between postpartum fatigue and breastfeeding motivation among postpartum mothers who attended Srikandi Husada Kudus Clinic. This study employed a cross-sectional design with a quantitative, observational-analytic approach. The sample consisted of postpartum mothers on days 3 to 7 after childbirth, selected purposively based on predetermined inclusion and exclusion criteria. Sample characteristics included age, education level, employment status, type of delivery, parity, and breastfeeding method. The variables analyzed were postpartum fatigue (independent) and breastfeeding motivation (dependent). Data were collected using standardized questionnaires and analyzed using univariate and bivariate methods, including the Spearman Rho test. The findings showed that most postpartum mothers on days 3 to 7 experienced severe postpartum fatigue with relatively low breastfeeding motivation. The results also indicated a tendency that the higher the fatigue experienced by mothers, the lower their motivation to breastfeed, particularly during the early postpartum phase. This study indicates that postpartum fatigue in the early puerperium is closely associated with low maternal motivation to breastfeed. Therefore, early identification of fatigue and optimization of breastfeeding support from the beginning of the postpartum period are necessary to improve breastfeeding success.